Using Big Data in Healthcare Context: a Conceptual Study - Ali Saare, Murtaja; Mohammed Jasim, Osamah; Ahmed Mahdi, Alia; Hussain, Azham (International Journal of Engineering and Technology, 2018)
The most significant phenomenon that has caught the attention of the modern computing industry nowadays since the â€œInternetâ€ is â€œBig Dataâ€. The technology platforms that have been developed together with it has allowed for the processing of data of various formats and structures without having to worry about the constraints that are linked with traditional systems and database platforms. In this conceptual paper, the researchers sought to discuss an overview of the elements associated with this phenomenon. Thereafter, the benefits of using big data in the healthcare field are highlighted. Based on prior literature, there is a paucity of research on the healthcare context whether theoretically or empirically. Most of the previous studies have focused on Big Data in general.Â